2014
DOI: 10.1183/09031936.00085614
|View full text |Cite
|
Sign up to set email alerts
|

Nasopharyngeal gene expression, a novel approach to study the course of respiratory syncytial virus infection

Abstract: Respiratory syncytial virus (RSV) causes mild infections in the vast majority of children. However, in some cases, it causes severe disease, such as bronchiolitis and pneumonia. Development of severe RSV infection is determined by the host response. Therefore, the main aim of this study was to identify biomarkers associated with severe RSV infection.To identify biomarkers, nasopharyngeal gene expression was profiled by microarray studies, resulting in the selection of five genes: ubiquitin D, tetraspanin 8, mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…By investigating whole blood [4346] and upper airway gene expression profiles [47], researchers demonstrated overexpression of interferon-related pathway in children with severe RSV infection compared to healthy controls or mild RSV infection. Furthermore, Mejias et al ., by examining whole blood transcriptome from children with severe bronchiolitis either by RSV, rhinovirus, or influenza in the U.S. and Finnish cohorts, observed pathogen-specific transcriptional signatures [43].…”
Section: Endotyping Bronchiolitismentioning
confidence: 99%
“…By investigating whole blood [4346] and upper airway gene expression profiles [47], researchers demonstrated overexpression of interferon-related pathway in children with severe RSV infection compared to healthy controls or mild RSV infection. Furthermore, Mejias et al ., by examining whole blood transcriptome from children with severe bronchiolitis either by RSV, rhinovirus, or influenza in the U.S. and Finnish cohorts, observed pathogen-specific transcriptional signatures [43].…”
Section: Endotyping Bronchiolitismentioning
confidence: 99%
“…Demographics and clinical parameters were collected from questionnaires and medical records. Within 24 h after admission, a blood sample and a nasopharyngeal aspirate (NPA) sample were collected as previously described (9). The mean age of the patients was 53 days, the average gestational age was 38 weeks, and 48% of the patients were male (Table 1).…”
mentioning
confidence: 99%
“…Most respiratory viral mechanistic studies have been performed using influenza viruses, RSV, HRV and coronaviruses [80][81][82][83]. Using BEC, the common and demonstrated that the pattern of innate immune activation was both host cell and viral strain specific [85].…”
Section: Mechanisms Of Diseasementioning
confidence: 99%
“…A number of studies have been undertaken to understand the pathogenesis of severe RSV in young children and have identified a variety of gene expression patterns in blood including under expression of T cell cytotoxicity/NK cells and plasma cell genes, as well as upregulation of JAK/STAT, prolactin, IL-9 signaling, cell to cell signaling, and immune activation pathways [79,92]. Using nasal epithelial gene expression analysis, van den Kieboom identified 5 differentially expressed genes in 30 children with mild, moderate and severe RSV infection [81]. Ubiquitin D, tetraspanin 8, mucin 13, β microseminoprotein, chemokine ligand 7 were up regulated and differentiated mild from severe illness.…”
Section: Respiratory Syncytial Virusmentioning
confidence: 99%